Pengaruh Capital Adequacy Ratio (CAR), Likuiditas dan Efisiensi Operasional terhadap Profitabilitas Perusahaan Perbankan yang Terdaftar di BEI - Erni Masdupi; Defri - (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2012)
This research aimed to analize the effect of capital adequacy ratio (CAR), liquidity (loan to deposit ratio-LDR), operational efficiency (BOPO) of profitability (return on assets-ROA) at banking companies listed on the Indonesia Stock Exchange (IDX). This research is research kausatif with a population of listed banking company in BEI. Methods of analysis used is multiple regression analysis. The results of the study shows that CAR has positive and no significant effect on ROA in the banking companies that listed on the BEI, LDR has positive and no significant effectt on ROA in the banking companies that listed on the BEI, and BOPO has negative and significant effect on ROA in the banking companies that listed on the BEI.